A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
if f(x)= x+3 / 4 (x+3 over 4), what is the equation for f^–1(x)?
a. f^–1(x) = 4(x  3)
b. f^–1(x) = 4x + 3
c. f^–1(x) = 4(x + 3)
d. f^–1(x) = 4x  3
anonymous
 one year ago
if f(x)= x+3 / 4 (x+3 over 4), what is the equation for f^–1(x)? a. f^–1(x) = 4(x  3) b. f^–1(x) = 4x + 3 c. f^–1(x) = 4(x + 3) d. f^–1(x) = 4x  3

This Question is Closed

Jhannybean
 one year ago
Best ResponseYou've already chosen the best response.0\[f(x)=\frac{x+3}{4\left(\dfrac{x+3}{4}\right)}\]Is this your problem?

jdoe0001
 one year ago
Best ResponseYou've already chosen the best response.0\(\bf f(x)={\color{blue}{ y}}=\cfrac{{\color{brown}{ x}}+3}{4} \quad \textit{do the switcharoo baby}\quad {\color{brown}{ x}}=\cfrac{{\color{blue}{ y}}+3}{4}\impliedby f^{1}(x)\)

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0\[f(x) = \frac{ x+3 }{ 4 }\]

campbell_st
 one year ago
Best ResponseYou've already chosen the best response.0so the function is \[y = \frac{x + 3}{4}\] to find the inverse swap x and y \[x = \frac{y + 3}{4}\] now make y the subject of the equation

Jhannybean
 one year ago
Best ResponseYou've already chosen the best response.0Oh I simply read it wrong, whoops.
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.